What is the current evidence for the relationship between the climate and environmental crises and child marriage? A scoping review - Daniel H. Pope; Heather McMullen; Angela Baschieri; Anandita Philipose; Chiagozie Udeh; Julie Diallo; David McCoy (Taylor & Francis Group, 2023)
ABSTRACTEnvironmental crises such as climate change threaten the realisation of sexual and reproductive health and rights. In this scoping review, we examine the evidence for the relationship between environmental crises and child marriage. We conducted a search of Google Scholar, Scopus and MedLine from their origin to 4th June 2021 for both peer-reviewed academic literature and 'grey' literature. A total of 24 relevant articles were identified, including both quantitative and qualitative work. while there are limitations of the current evidence base such as its narrow geographical scope, we find that environmental crises worsen known drivers of child marriage, pushing families to marry their daughters early through loss of assets and opportunities for income generation, displacement of people from their homes, educational disruption, and the creation of settings in which sexual violence and the fear of sexual violence increase. Local socio-cultural contexts such as bride price or dowry practices further shape how these factors affect child marriage. Given many of the areas with the highest current rates of child marriage face the gravest environmental threats, action to tackle child marriage must take account of the link identified in this review.